Earthwork activities in private housing industry - Lam, Yuen Siong (2005)
The success and failure of a housing project depends on the earthwork activities as it is the first activity in any housing development project. In many instances, many unforeseen circumstances that affect the estimates of plant performance, output, and hence the duration of activities, fall short of the actual situation once construction start. The purpose of this study is to study the earthmoving operation in a private housing development project, to study the earthmoving production in a private housing development project, to identify the problems faced by the contractors during the earthmoving activities and to identify the factors that influence the contractors pricing during bidding. Data was gathered from the local construction organizations by means of a survey questionnaire which was further analyzed using the average index computation to portray the ranking of the associated factors. A comparison of earthmoving production using the average cycle time based on earthmoving production estimating table and the motion and time study conducted at one of the project site. The finding revealed that generally earthwork procedure for private housing project does not emphasize on the environmental and quality control and thus the works carried out do not follow the standard JKR specification. It was apparent that there is not much variation from the earthmoving production estimating table for the excavator cycle time as compare to the excavator cycle time from the motion and time study during construction. The main problems that the contractor faced stem from the client’s decision and confirmation on the final platform levels of the projects, the design provided by the consultant and the inaccurate survey information. The final pricing during bidding was highly influence by the client’s reputation to pay and the financial status which normally depends on the sale of the houses built